2020
DOI: 10.3201/eid2611.202263
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SARS-CoV-2 Transmission in Different Settings, Brunei

Abstract: We report the transmission dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) across different settings in Brunei. An initial cluster of SARS-CoV-2 cases arose from 19 persons who had attended the Tablighi Jama’at gathering in Malaysia, resulting in 52 locally transmitted cases. The highest nonprimary attack rates (14.8%) were observed from a subsequent religious gathering in Brunei and in households of attendees (10.6%). Household attack rates from symptomatic case-patients were higher (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 19 publications
7
96
3
Order By: Relevance
“…We identified 54 relevant published studies that reported household secondary transmission, with 77 758 participants (eTable 1 in the Supplement ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 A total of 16 of 54 studies (29.6%) were at high risk of bias, 27 (50.0%) were moderate, and 11 (20.4%) were low (eTable 2 in the Supplement ). Lower quality was attributed to studies with 1 or fewer test per contact (35 studies [64.8%]), small sample sizes (31 [57.4%]), a...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 54 relevant published studies that reported household secondary transmission, with 77 758 participants (eTable 1 in the Supplement ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 A total of 16 of 54 studies (29.6%) were at high risk of bias, 27 (50.0%) were moderate, and 11 (20.4%) were low (eTable 2 in the Supplement ). Lower quality was attributed to studies with 1 or fewer test per contact (35 studies [64.8%]), small sample sizes (31 [57.4%]), a...…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 summarizes secondary attack rates for 44 studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 61 , 62 , 63 , 65 , 66 , 67 , 69 , 70 of household contacts and 10 of family contacts. 26 , 31 , 37 , 45 , 58 , 60 , 65 , 68 , 71 , 72 Estimated mean secondary attack rate for household contacts was 16.4% (95% CI, 13.4%-19.6%) and family contacts was 17.4% (95% CI, 12.7%-22.5%). One study 40 restricted index cases to children (age <18 years), resulting in a substantially lower secondary attack rate of 0.5%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our results show that can be this high for events of this type, and that is still an important piece of information for planners. Heterogeneity in transmission and “superspreading events” is increasingly recognized in infectious disease and in COVID-19 ( 10 , 11 ), and “chopping off the tail” has recently been proposed as a way to reduce transmission considerably ( 12 ). Substantially reducing the upper tail of large and rapid clusters requires planning for precisely the infectious index cases that lead to large reported outbreaks (such as those described here).…”
Section: Sources Of Biasmentioning
confidence: 99%